Antiflammin-1 attenuates bleomycin-induced pulmonary fibrosis in mice - Liu, Wei (BioMed Central, 2013)
BACKGROUND: Antiflammin-1 (AF-1), a derivative of uteroglobin (UG), is a synthetic nonapeptide with diverse biological functions. In the present study, we investigated whether AF-1 has a protective effect against bleomycin-induced pulmonary fibrosis. METHODS: C57BL/6 mice were injected with bleomycin intratracheally to create an animal model of bleomycin-induced pulmonary fibrosis. On Day 7 and Day 28, we examined the anti-inflammatory effect and antifibrotic effect, respectively, of AF-1 on the bleomycin-treated mice. The effects of AF-1 on the transforming growth factor-beta 1 (TGF-β1)-induced proliferation of murine lung fibroblasts (NIH3T3) were examined by a bromodeoxycytidine (BrdU) incorporation assay and cell cycle analysis. RESULTS: Severe lung inflammation and fibrosis were observed in the bleomycin-treated mice on Day 7 and Day 28, respectively. Administration of AF-1 significantly reduced the number of neutrophils in the bronchoalveolar lavage fluid (BALF) and the levels of tumor necrosis factor-alpha (TNF-α) and interleukin-1 beta (IL-1β) in the lung homogenates on Day 7. Histological examination revealed that AF-1 markedly reduced the number of infiltrating cells on Day 7 and attenuated the collagen deposition and destruction of lung architecture on Day 28. The hydroxyproline (HYP) content was significantly decreased in the AF-1-treated mice. In vitro, AF-1 inhibited the TGF-β1-induced proliferation of NIH3T3 cells, which was mediated by the UG receptor. CONCLUSIONS: AF-1 has anti-inflammatory and antifibrotic actions in bleomycin-induced lung injury. We propose that the antifibrotic effect of AF-1 might be related to its suppression of fibroblast growth in bleomycin-treated lungs and that AF-1 has potential as a new therapeutic tool for pulmonary fibrosis.